Reliability of LED's; Are the Accelerated Ageing Tests Reliable?. (1982) - Ferenczi, George
Abstract : The mechanisms, leading to light output degradation of LED's were studied using a number of different techniques e.g. deep level spectroscopy, electroluminescence, minority carrier life time measurements. Several processes were revealed having different temperature and stress current dependence. Using these data extrapolations based on accelerated ageing test results are reexamined.